The Effectiveness of Drones in Improving Efficiency and Accuracy of Oil Palm Plantation Management in Indonesia: A Literature Review - Briliyanti, Rahma Dita; Maulana, Iqbal; Jannah, Erana Misbahul; Purboseno, Sentot (ARRUS Journal of Engineering and Technology, 2025)
Oil palm plantation management in Indonesia faces significant challenges in terms of operational efficiency, land monitoring accuracy, and compliance with sustainability standards. With the advancement of digital technology, the use of drones or Unmanned Aerial Vehicles (UAVs) has emerged as a potential solution to enhance plantation management effectiveness. This study aims to examine the effectiveness of drones in supporting oil palm plantation management in Indonesia through a review of both national and international literature. The findings indicate that drones can provide high-resolution spatial data quickly and accurately, which can be integrated with Geographic Information Systems (GIS) for planting block mapping, crop growth monitoring, pest infestation detection, and land fertility evaluation. Several studies have reported mapping efficiency improvements of up to 60%, along with support for sustainability reporting such as ISPO and RSPO. The use of drones also supports precision agriculture approaches, particularly in variable-rate fertilization and zonal land management. Despite implementation challenges such as investment costs and a shortage of trained operators, drone technology holds significant potential for the digitalization of plantations. This review recommends enhancing UAV adoption through technical training, strengthening digital infrastructure, and formulating supportive operational regulations. The integration of drones into oil palm plantation management is believed to accelerate the transformation toward a more efficient, accurate, and sustainable precision agriculture system.